GAMBARAN PSYCHOLOGICAL WELL - BEING PADA BIARAWATI DALAM HIDUP MEMBIARA - Apriyeni Sinabutar; Hotpascaman Simbolon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the psychological well-being of nuns in religious life, particularly in dealing with convent rules, adaptation within the community, and various psychological challenges in daily life. This study employed a qualitative method with a phenomenological approach. The participants consisted of two nuns from the Congregation of the Sisters of Saint Joseph (KSSY) Hayam Wuruk Medan, who were selected using purposive sampling. Data were collected through in-depth interviews, observation, and documentation. The data were analyzed thematically based on Ryff’s six dimensions of psychological well-being, namely self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth.The results showed that both participants demonstrated psychological well-being in their religious life, although they experienced different dynamics. Participant 1 developed psychological well-being primarily through long-term personal experiences and struggles, including illness, doubts about her vocation, the process of self-acceptance, and the ability to maintain her commitment to religious life. Meanwhile, Participant 2 demonstrated psychological well-being mainly through the formation process, communal living experiences, adaptation to differences in personality and seniority, and changes in attitudes and personality. Both participants demonstrated the ability to establish positive relationships, fulfill responsibilities within the community, maintain a sense of purpose related to their vocation and service, and experience personal growth. Thus, psychological well-being among nuns develops through self-acceptance, social relationships, environmental adaptation, meaning and commitment to their vocation, as well as formation experiences and personal growth within religious life.